IDENTIFICATION OF POTENTIAL ANTIVIRUS FROM Moringa oleifera LEAF AS MPRO SARS-COV-2 INHIBITOR: STUDY OF MOLECULAR DOCKING - Zaimi Afandi; Yuni Rahmayanti; Rizarullah Rizarullah (FKIP USK, 2022)
Corona virus disease/COVID-19 is an acute respiratory infection caused by SARS-CoV-2 and has become a pandemic. COVID-19 can be prevented by efforts such as physical distancing, washing hands, using masks and self-isolation as well as regional isolation. Moringa is a plant that can be used both as food and medicine. The purpose of this study was to observe the activity of Moringa leaf compounds in inhibiting Mpro (main protease) SARS-CoV-2. Moringa leaf compounds tested were Gamma tocopherol, Benzyl glucosinolate and Chlorogenic acid. The compound was taken from pubchem, while Mpro SARS-CoV-2 (receptor) was obtained from the world protein bank with the PDB code 6W63. This research was conducted using the In Silico method and AutoDock Vina software was used for the tethering process. The results of gridbox optimization by re-tethering control ligands obtained RMSD results of 0.122 . The results showed free energy Gibbs (ΔG) Gamma tocopherol (-6.8 kcal/mol), Benzyl glucosinolat (-6.6 kcal/mol), and Chlorogenic acid (-7.0 kcal/mol) which indicated a stable inhibitory reaction of Moringa leaf compounds against Mpro SARS-CoV-2. Based on Lipinski's rules, the compounds from Moringa leaves tested were qualified to be used as herbal medicines to be used orally.